2016
DOI: 10.1080/15384101.2015.1120926
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of rpL3 in cell response to nucleolar stress induced by Act D in tumor cells lacking functional p53

Abstract: Many chemotherapeutic drugs cause nucleolar stress and p53-independent pathways mediating the nucleolar stress response are emerging. Here, we demonstrate that ribosomal stress induced by Actinomycin D (Act D) is associated to the up-regulation of ribosomal protein L3 (rpL3) and its accumulation as ribosome-free form in lung and colon cancer cell lines devoid of p53. Free rpL3 regulates p21 expression at transcriptional and post-translational levels through a molecular mechanism involving extracellular-signal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…In fact the loss of rpL3 makes chemotherapeutic drug ineffective. We have demonstrated that ectopic expression of rpL3 in cancer cells induces cell cycle arrest or apoptosis by positively modulating p21 expression at transcriptional and post-translational levels1617. Moreover, we found that rpL3 status was associated to chemoresistance since the loss of rpL3 makes chemotherapeutic drugs, such as 5-FU, oxaliplatin, actinomycin D and cisplatin ineffective41635.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In fact the loss of rpL3 makes chemotherapeutic drug ineffective. We have demonstrated that ectopic expression of rpL3 in cancer cells induces cell cycle arrest or apoptosis by positively modulating p21 expression at transcriptional and post-translational levels1617. Moreover, we found that rpL3 status was associated to chemoresistance since the loss of rpL3 makes chemotherapeutic drugs, such as 5-FU, oxaliplatin, actinomycin D and cisplatin ineffective41635.…”
Section: Discussionmentioning
confidence: 92%
“…2A shows that 5-FU treatment caused a decrease of CBS expression levels. Next, to investigate the role of rpL3, we performed analogous experiments in a cell clone namely rpL3ΔCalu-6 cells in which rpL3 is stably silenced16. In these cells, 5-FU failed to downregulate CBS expression levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, RPL3-mediated positive regulation of p21 expression via ERK (extracellular-signal-regulated kinase) activation results in promotion of apoptosis as well as reduction of proliferation and migration of these cancer cells (Russo et al 2016a). In a similar experimental system, the use of 5-FU, DNA, and RNA synthesis inhibitor in combination with RPL3 overexpression considerably enhances sensitivity of 5-FU-resistant lung and colon cancer cells to this drug, and thereby, it strongly increases cytotoxic effect by means of the mitochondrial apoptotic cell response which prevents cell migration and invasion.…”
Section: Nucleolus-mediated Anticancer Strategiesmentioning
confidence: 84%
“…Chemotherapy drugs constitute another category of cell cycle regulators (Russo et al 2016; Li et al 2016), among which paclitaxel is widely used to treat various types of cancer (Pazdur et al 1993). Paclitaxel promotes the assembly of microtubules and inhibits their disassembly (Pazdur et al 1993).…”
Section: Nanoparticles For Radiosensitizationmentioning
confidence: 99%